1997
DOI: 10.3406/intel.1997.1544
|View full text |Cite
|
Sign up to set email alerts
|

Une approche de l'olfaction : du linguistique au neuronal

Abstract: Ce texte est une introduction au dossier sur l'olfaction. Il situe d'abord très brièvement, à travers le résumé des quelques revues de questions sur le domaine, les principales perspectives de recherches actuelles qui s'inscrivent dans une perspective cognitive. Il décrit les principales difficultés rencontrées lors de la mise en place d'un programme pluridisciplinaire sur l'olfaction et introduit les articles qui, dans ce cadre, ont alimenté notre réflexion et conduit à questionner les paradigmes cognitifs cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although experts are known not only to acquire a systematic knowledge of the chemistry of odorants but also to learn to describe olfactory qualities of odorants and odor sources in a shared language, very little is known about the importance of hedonic processing in both the ways: (i) they describe but also (ii) they perceive smells. On a descriptive level, the literature in the field suggests that whereas pleasantness is a prominent attribute that drives odor verbalizations (Dubois and Rouby, 1997; Dubois, 2000), experts may be inclined to avoid any reference to pleasantness (Yoshida, 1964; Ehrlichman and Bastone, 1992; Holley, 2002). In the present study, we aim to test experimentally this hypothesis on a verbal level and to further assess how expertise modulates hedonic perception of odors.…”
Section: Introductionmentioning
confidence: 99%
“…Although experts are known not only to acquire a systematic knowledge of the chemistry of odorants but also to learn to describe olfactory qualities of odorants and odor sources in a shared language, very little is known about the importance of hedonic processing in both the ways: (i) they describe but also (ii) they perceive smells. On a descriptive level, the literature in the field suggests that whereas pleasantness is a prominent attribute that drives odor verbalizations (Dubois and Rouby, 1997; Dubois, 2000), experts may be inclined to avoid any reference to pleasantness (Yoshida, 1964; Ehrlichman and Bastone, 1992; Holley, 2002). In the present study, we aim to test experimentally this hypothesis on a verbal level and to further assess how expertise modulates hedonic perception of odors.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies suggest that an odor can be named with different verbal labels that may evoke different contexts [Howes, ]. Whereas odors are usually named by their contextual source objects, Engen noted that “With respect to subject generated odor names, it has been observed that odors are customarily labeled in terms of personal contextual reference and not by invariant source names” [Dubois and Rouby, ]. One may cite for example, “the smell of my grandmother's cakes,” “the medicine for coughs that my mother rubbed on my chest,” “my daddy's aftershave,” etc.…”
Section: Introductionmentioning
confidence: 99%
“…It seems, in Western societies at least, that odors -unlike colorswere not constructed collectively via negotiation of a shared meaning during verbal interaction (Dubois & Rouby, 1997). According to Schaal (2004), it is as if ''the acquisition of chemical sensory knowledge were the random outcome of personal experiences".…”
Section: Introductionmentioning
confidence: 99%